Analysis of the competitiveness of soybean production in Benin - Kpenavoun Chogou, Sylvain; Tossou, Bignon William; Sossou, Comlan Hervé (My University, 2022)
With the increase in its production and its prized label, Beninese soybeans are increasingly targeting the Chinese and European markets. It is then essential, to be able to take advan- tage of the market and to produce better by being competitive. This study goes beyond a simple profitability analysis to analyse the competitiveness of soybean production in Benin (based on the domestic resource cost ratio) and the factors on which it depends. Data used concern 967 soybean-producing farms from two agricultural development regions. Produc- ing nearly 89% of the national soybean production, these regions have been identified for the promotion of soybean cultivation by the Beninese government. Policy Analysis Matrix and binomial logistic regression were used to analyse these data. The results showed that soybean production is profitable from both a financial and economic perspective. The Do- mestic Resource Cost Ratio was estimated at 0.55, indicating that the farms studied are globally competitive. The microeconomic analysis reveals that more than two-thirds of the farms in the study area are competitive. Investment in formal education for farm man- agers; public and private investment in infrastructure, particularly market infrastructure, technical innovations, and information transfer; and facilitating access to agricultural ad- vice are factors on which the various stakeholders can act to improve farm competitive- ness.
Keywords: Benin; Policy analysis matrix; Competitiveness; Soybeans; Determinants